Efforts for Treatment of Caesaria Section Scars in Postpartum Mother - Sari, Ponco Indah Arista (MultiTech Publisher, 2024)
Cesarean section is usually performed in an emergency or is a choice without any indication of saving the lives of the mother and baby. According to some people, this surgical method has a long healing period compared to normal delivery. The wounds caused also have a different healing period compared to healing perineal tears that have been stitched. The research aims to describe the various efforts made by postpartum mothers to deal with wounds after undergoing a cesarean section. The research method uses a qualitative approach with interview and observation methods. Postpartum mothers were selected as participants using purposive sampling techniques. The data collection technique was carried out through interviews and observations of 10 post-partum mothers and post-partum mothers. The interview questionnaire has set question points based on several references and literature reviews. The results of this research show that postpartum mothers have several efforts to treat SC scars. The need for assistance from health workers for postpartum mothers, so that postpartum mothers have the ability and obtain health information according to their needs. Assistance is carried out by looking at current developments in aesthetic care according to women's needs in all life cycles